Prodromal Parkinsonian Features in Carriers of Gaucher Disease Compared to Controls - Michal Becker-Cohen; Ari Zimran; Tama Dinur; Maayan Tiomkin; Arndt Rolfs; David Arkadir; Peter Bauer; Elena Shulman; Gilad Yahalom; Mikhal E. Cohen; Orly Manor; Ora Paltiel; et al. (Life, 2025)
Carriers of Gaucher disease have an increased risk of developing Parkinson’s disease (PD). Identifying PD in its prodromal stage is crucial, as early detection before motor symptoms appear allows for potential interventions to salvage neurons and slow or prevent disease progression. At the Gaucher unit at Shaare Zedek Medical Center, we are following a large cohort of obligatory carriers of GBA1 variants (GBA1 carriers) and study ways to identify those at an increased risk for developing PD. In this study, we compared non-invasive prodromal PD tests in 164 GBA1 carriers and 49 participants with no genetic predisposition to PD (controls). The proportion of abnormal tests was compared between groups, and the risk factors for having abnormal tests (at least one or ≥20%) were studied. There were no differences between GBA1 carriers and controls in the frequency of abnormalities, having at least one abnormal test or having ≥20% abnormal tests. Having ≥20% of abnormal tests was associated mainly with age. Principal component analysis identified distinct cognitive, motor, and non-motor dysfunction patterns in GBA1 carriers compared to controls, with cognition in GBA1 carriers more closely linked to motor dysfunction and less influenced by mood and sleep, while in controls, executive function was tied to emotional state and fatigue. Younger carriers outperformed older ones in motor and some cognitive tasks. Those with a family history of PD showed worse cognitive scores than participants with no family history. Sex-based analysis revealed males obtained higher scores in most of the cognition subtests of the NeuroTrax test, whereas it was females in motor and other cognitive domains, mainly in the group of GBA1 carriers. A longitudinal follow-up of GBA1 carriers is ongoing to understand PD progression in GBA1 carriers with the aim of offering targeted intervention for those at higher risk.